2000
DOI: 10.1017/s0960258500000143
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation-induced dormancy in papaya (Carica papayaL.) seeds is alleviated by heat shock

Abstract: The effects of desiccation and temperature on the germination capability of Carica papaya L. were investigated for seeds extracted from three commercial fruit batches. More than 50% of freshly isolated, cleaned (sarcotesta removed) but undried seeds germinated at 26°C. However, desiccation to approx. 20% seed RH reduced germination at this temperature to < 10%. A substantial increase in germination at alternating temperatures (33/19°C) indicated that desiccation induced seed dormancy rather than viability loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 30 publications
6
35
1
3
Order By: Relevance
“…Further work by Ashmore et al (unpublished) on S. luehmannii indicates that seeds are tolerant to desiccation to around 20% MC but also require dormancy-breaking treatments (gibberellic acid or heat shock) to achieve germination (68% and 82%, respectively). This is similar to reports in papaya seeds, where desiccation tolerance was observed down to 5% MC, but dormancy-breaking treatments were subsequently required for germination (Wood et al 2000a;Ashmore et al 2009). Shatnawi et al (2004) have also reported both in vitro propagation and shoot-tip cryopreservation via encapsulation-dehydration of Syzygium francisii (rose satinash) (Table 1).…”
Section: Socio-economically Important Rainforest Taxasupporting
confidence: 89%
“…Further work by Ashmore et al (unpublished) on S. luehmannii indicates that seeds are tolerant to desiccation to around 20% MC but also require dormancy-breaking treatments (gibberellic acid or heat shock) to achieve germination (68% and 82%, respectively). This is similar to reports in papaya seeds, where desiccation tolerance was observed down to 5% MC, but dormancy-breaking treatments were subsequently required for germination (Wood et al 2000a;Ashmore et al 2009). Shatnawi et al (2004) have also reported both in vitro propagation and shoot-tip cryopreservation via encapsulation-dehydration of Syzygium francisii (rose satinash) (Table 1).…”
Section: Socio-economically Important Rainforest Taxasupporting
confidence: 89%
“…Germination of ~70% of desiccated C. papaya seeds could be achieved by giving seeds a 2–6 h HS before returning them to ∼25 °C for relatively rapid and synchronous germination. In contrast, heat treatment had no effect on the dormancy behaviour of the desiccated C. papaya seed without prior imbibition, irrespective of variation in temperature and duration of treatment (Wood et al , 2000). Thus, hydration is an absolute prerequisite as germination subsequently occurred only in seeds previously imbibed for 1–5 d prior to HS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Carica papaya L. (papaya) is an opportunistic pioneer species native to tropical South America and is an important commercial crop of tropical regions worldwide. Seeds readily germinate when fresh from the fruit but germination is slow and erratic after desiccation (Wood et al , 2000) or in the presence of the sarcotesta, which contains germination inhibitors (Lange, 1961; Chow and Lin, 1991). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations